2017
DOI: 10.1007/s12665-017-6742-2
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of soil enzymes and spring barley to copper chloride and copper sulphate

Abstract: Study was carried out to compare the effect of the degree of contamination of soil with copper on the soil enzyme activity, depending on the type of chemical compound with which a metal reaches the soil and on the method of soil use. An effect of increasing doses of copper on growth and the development of spring barley has been studied. The study was carried out as a pot experiment on two types of soil: loamy sand and light loam. Copper was introduced to soil as copper(II) sulphate(VI) and copper(II) chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The conducted study showed that the application of high doses of copper reduces the enzymatic activity of the soil, which indirectly reduces its fertility and capability, which is its measure according to Russel (2005). The negative effect of soil contamination with copper on its enzymatic activity is highlighted in studies by Chaperon and Sauvé (2007), Wang et al (2007), Fernandéz-Calvińo et al (2010, Zhan and Sun (2014), Wyszkowska et al (2017), andLi et al (2018). The inactivating effect of this metal on the activity of urease, dehydrogenases and alkaline phosphatase increased with the increase of its dose.…”
Section: Resultsmentioning
confidence: 94%
“…The conducted study showed that the application of high doses of copper reduces the enzymatic activity of the soil, which indirectly reduces its fertility and capability, which is its measure according to Russel (2005). The negative effect of soil contamination with copper on its enzymatic activity is highlighted in studies by Chaperon and Sauvé (2007), Wang et al (2007), Fernandéz-Calvińo et al (2010, Zhan and Sun (2014), Wyszkowska et al (2017), andLi et al (2018). The inactivating effect of this metal on the activity of urease, dehydrogenases and alkaline phosphatase increased with the increase of its dose.…”
Section: Resultsmentioning
confidence: 94%
“…This is indicative of a feedback between bacterial community and activity of oxidoreductases, because these are the microorganisms that trigger the enhancement in the activity of dehydrogenases [ 100 , 101 ]. The latter directly reflects the activity of soil microorganisms [ 102 , 103 ] because dehydrogenases are endogenous enzymes responsible for bio-oxidation of soil organic matter [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…It consists in determining variables constituting a linear combination of the tested variables [ 25 ]. The application of PCA enabled a precise determination of the scale of changes of coal tar creosote and rhamnolipids impact factors on the soil environment [ 26 ].To perform statistical analyses, Statistica 13.3 software (Statsoft Inc.) was used.…”
Section: Methodsmentioning
confidence: 99%